2021
DOI: 10.1186/s41983-021-00284-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antinuclear antibody in patients with multiple sclerosis: a case-control study

Abstract: Background Antinuclear antibody (ANA) is a common test for excluding alternative diagnoses. However, the significance of ANA testing in patients with multiple sclerosis (MS) remains unclear. Objectives To compare the prevalence of positive ANA antibody and its titer between patients with MS (cases) and non-MS patients who attended neurology clinics (control) in Saudi Arabia. Methods A case-control revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“… 26 Serum antinuclear antibody can be mildly elevated in patients with MS, but at rates similar to the general population. 27 Anti-aquaporin-4 and anti-MOG tests are recommended for patients with optic neuritis, 28 tumefactive brain lesions, or longitudinally extensive spinal cord lesions (>3 segments) to detect NMO and MOG-associated disorder. Current research has found that serum neurofilament light chain has potential efficacy as a biomarker for ongoing inflammatory activity, although this test currently has restricted availability.…”
Section: Ms Diagnosismentioning
confidence: 99%
“… 26 Serum antinuclear antibody can be mildly elevated in patients with MS, but at rates similar to the general population. 27 Anti-aquaporin-4 and anti-MOG tests are recommended for patients with optic neuritis, 28 tumefactive brain lesions, or longitudinally extensive spinal cord lesions (>3 segments) to detect NMO and MOG-associated disorder. Current research has found that serum neurofilament light chain has potential efficacy as a biomarker for ongoing inflammatory activity, although this test currently has restricted availability.…”
Section: Ms Diagnosismentioning
confidence: 99%